Leading the Digital Revolution Examining the Impact of Digital Leadership on Work Performance and Organizational Commitment in the Kawasan Industri Mitra (KIM) - Honorata Ratnawati Dwi Putranti; Sulistiyani Sulistiyani (Jurnal Manajemen Industri dan Logistik, 2023)
This research aims to examine and analyze the effect of digital leadership on work performance through organizational commitment. The research population is all employees in the Mitra Industrial Area (KIM) Karawang, West Java. A total of 214 samples were taken using random sampling. The digital leadership variable uses two dimensions with three indicators each, the organizational commitment variable uses three dimensions with three indicators each, and the work performance variable uses three indicators. The results obtained show a positive and significant effect of digital era leadership on work performance and a positive and significant effect of organizational commitment on work performance. These results are analyzed together with the dimensions used. The results obtained from leadership in the employee dimension are greater than the innovation focus dimension. The greatest organizational commitment is in the normative commitment dimension.